Development Of Plant Waste Ecoprint Techniques For Environmentally Friendly Fabric Dyeing In Tonsaru Village - Abdullah, Susanti; Sumolang, Nortje; Tangkere, Telly F.S. (Journal of Innovative and Creativity, 2026)
The textile industry is one of the largest contributors to environmental pollution due to the use of synthetic dyes. As an environmentally friendly solution, the ecoprint technique utilizes natural pigments derived from plants. This study aims to develop an ecoprint technique by utilizing plant waste available in Tonsaru Village to produce aesthetic and sustainable textile products. This research employed a Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The plant waste used in this study included cassava leaves (Manihot esculenta) as motif printing materials and fountain plant flowers (Russelia equisetiformis) as natural dye sources. The development process involved a pounding technique to transfer leaf motifs, followed by a boiling technique in which the fabric was boiled together with flower waste to maximize color absorption. An initial mordanting stage using alum and lime solutions was applied to ensure strong pigment fixation on the fabric fibers. The results showed that the plant waste–based ecoprint technique successfully produced textile products in the form of a wrap skirt fabric with clear motifs and long-lasting colors. The utilization of local plant waste proved to be effective as an alternative natural dye, supporting the zero waste principle and reducing the negative environmental impact of organic waste burning. This study concludes that innovations in ecoprint techniques using plant waste have great potential for development in the sustainable creative industry